2012
DOI: 10.1111/j.1365-2761.2012.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel genotyping technique for distinguishing between Flavobacterium psychrophilum isolates virulent and avirulent to ayu, Plecoglossus altivelis altivelis (Temminck & Schlegel)

Abstract: We developed a simple genotyping method for Flavobacterium psychrophilum for analysing two single nucleotide polymorphisms (SNPs) in the gyrA gene and to distinguish between isolates that are virulent and avirulent to ayu, Plecoglossus altivelis altivelis (Temminck & Schlegel). The genotyping method is an on/off switch assay and is based on the polymerase chain reaction technique with phosphorothioated primers. We classified 232 isolates from four families of fish (i.e. Plecoglossidae, Osmeridae, Cyprinidae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Strains in these three CC showed various levels of virulence against ayu in bath infection challenges and strains from CC-ST48/CC-ST56 generally seem more virulent than those from CC-ST52 [14]. Of note, CC-ST56 also infects cyprinids in Japan and [14] reported that ST-51 isolates from cyprinids cause mortality in ayu by bath infection challenge, providing experimental support for the possibility of transfer between carp and ayu in CC-ST56.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains in these three CC showed various levels of virulence against ayu in bath infection challenges and strains from CC-ST48/CC-ST56 generally seem more virulent than those from CC-ST52 [14]. Of note, CC-ST56 also infects cyprinids in Japan and [14] reported that ST-51 isolates from cyprinids cause mortality in ayu by bath infection challenge, providing experimental support for the possibility of transfer between carp and ayu in CC-ST56.…”
Section: Resultsmentioning
confidence: 99%
“…The actual host range of F. psychrophilum is, however, not limited to salmonids [12], although the infection is apparently less severe in non-salmonids [13]. In Japan, F. psychrophilum has been reported on a number of local non-salmonid wild fish species [14-16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type A was detected only in isolates from ayu. Fujiwara-Nagata et al (10) identified four genotypes (G-C, A-T, A-C, and G-T) among 232 isolates using single-nucleotide polymorphism (SNP) analysis of the DNA gyrase subunit A ( gyrA ) gene. Type G-C showed strong pathogenicity to ayu, whereas the other three were not or only weakly pathogenic.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Also, some isolates from ayu harbor a 2.8-, 3.4-, or 4.1-kbp plasmid (6). Four genotypes—type G-C, type A-T, type A-C, and type G-T—are classified based on genotyping by single nucleotide polymorphism analysis of the DNA gyrase subunit A gene (7). Type G-C shows strong pathogenicity to ayu, whereas the other three exhibit no or weak pathogenicity.…”
Section: Genome Announcementmentioning
confidence: 99%